Empowering Diverse Learners through Design-Based Data Literacy Education: the Data Design Cycle Framework - Nico Kling; Chantal Kling; Emelie Schwill; Christian-Andreas Schumann; Sajal Kabiraj (Ubiquity Proceedings, 2023)
Data literacy is a vital life-skill that is becoming increasingly necessary in today's society. As such, public data literacy education must become a substantive component in teaching, requiring an appropriate pedagogical model. This paper aims to present a new definition for data literacy, as well as conceptual framework for public data literacy education, drawing from tenets of design-based education and synthesized principles of data literacy education from literature. The resulting framework is termed the Data Design Cycle, and emphasizes collaboration, communication, and the development of problem-solving skills. The model is highly adaptable to different educational environments and learning styles, making it easily integrable into a variety of educational settings, including traditional classroom-based learning, online learning, and experiential learning programs. Furthermore, by promoting the principles of public teaching of data literacy and a learner-centred approach, the Data Design Cycle ensures that data literacy education is accessible to heterogeneous learners from diverse educational and socioeconomical settings.